A Qualitative Study On The Communicative Needs, Expectations And Experiences During Covid-19 Pandemic: 65 Years And Over Ankara Sample - Nilüfer Pınar Kılıç; Besime Pınar Özdemir; Gilman Senem Gençtürk Hızal; Melike Aktaş (Connectist Istanbul University Journal of Communication Sciences)
This study examines the high-risk group of individuals age 65 and over who most frequently experience the negative consequences of Covid-19. We review their communicative needs and expectations, knowledge and informationsources, and risk information and knowledge patterns. We conducted semi-structured interviews with 47 people aged 65 and over residing in Ankara. We evaluated our results in the context of The Social Amplification of Risk Framework, considering the major communication stations disseminating risk information. We found that during the Covid-19 pandemic, individuals aged 65 and over accessed risk information through new media and traditional media, and interpersonal communication, especially with close family and children, served as a primary information source during the pandemic. The trust factor, particularly regarding medical expertise, was an essential criterion in evaluating information. The communicative needs and expectations changed for this high-risk group. The need for improved digital communication capabilities become apparent during the pandemic crisis. Suggestions that consider public perspectives and risk perceptions while incorporating the relationship between risks and communication processes may contribute to structuring impactful risk communication activities.